Recruitment of tube and pelle to signaling sites at the surface of the Drosophila embryo. - Towb, P.; Galindo, R.L.; Wasserman, S.A. (Development, 1998)
A signaling pathway initiated by activation of the transmembrane receptor Toll defines dorsoventral polarity in the Drosophila embryo. Toll, which is present over the entire surface of the embryo, is activated ventrally by interaction with a spatially restricted, extracellular ligand. Tube and Pelle then transduce the signal from activated Toll to a complex of Dorsal and Cactus. Here we demonstrate by an mRNA microinjection assay that targeting of either Tube or Pelle to the plasma membrane by myristylation is sufficient to activate the signal transduction pathway that leads to Dorsal nuclear translocation. Using confocal immunofluorescence microscopy we also show that activated Toll induces a localized recruitment of Tube and Pelle to the plasma membrane. Together, these results strongly support the hypothesis that intracellular signaling requires the Toll-mediated formation of a membrane-associated complex containing both Tube and Pelle.